VAR2CSA binding phenotype has ancient origin and arose before Plasmodium falciparum crossed to humans: implications in placental malaria vaccine design - Gangnard, Stéphane (Sci Rep, 2019)
VAR2CSA is a leading candidate for developing a placental malaria (PM) vaccine that would protect pregnant women living in malaria endemic areas against placental infections and improve birth outcomes. Two VAR2CSA-based PM vaccines are currently under clinical trials, but it is still unclear if the use of a single VAR2CSA variant will be sufficient to induce a broad enough humoral response in humans to cross-react with genetically diverse parasite populations. Additional immuno-focusing vaccine strategies may therefore be required to identify functionally conserved antibody epitopes in VAR2CSA. We explored the possibility that conserved epitopes could exist between VAR2CSA from the chimpanzee parasite Plasmodium reichenowi and Plasmodium falciparum sequences. Making use of VAR2CSA recombinant proteins originating from both species, we showed that VAR2CSA from P. reichenowi (Pr-VAR2CSA) binds to the placental receptor CSA with high specificity and affinity. Antibodies raised against Pr-VAR2CSA were able to recognize native VAR2CSA from different P. falciparum genotypes and to inhibit the interaction between CSA and P. falciparum-infected erythrocytes expressing different VAR2CSA variants. Our work revealed the existence of cross-species inhibitory epitopes in VAR2CSA and calls for pre-clinical studies assessing the efficacy of novel VAR2CSA-based cross-species boosting regimens.